Lnc-ITSN1-2, Derived From RNA Sequencing, Correlates With Increased Disease Risk, Activity and Promotes CD4+ T Cell Activation, Proliferation and Th1/Th17 Cell Differentiation by Serving as a ceRNA for IL-23R via Sponging miR-125a in Inflammatory Bowel Disease - Nie, Jiayan; Zhao, Qiu (Frontiers in Immunology, 2020)
Background: This study aimed to investigate long-non-coding RNA (lncRNA) expression profiles and the correlation of lnc-ITSN1-2 expression with disease risk, activity and inflammation, and its influence on CD4+ T cell activation, proliferation, differentiation of inflammatory bowel disease (IBD). Methods: LncRNA expression profiles were detected in intestinal mucosa samples from 6 IBD patients and 6 health controls (HCs). Intestinal mucosa and PBMC lnc-ITSN1-2, IL-23R and inflammatory cytokines were measured in 120 IBD patients (60 Crohn’s disease (CD) and 60 ulcerative colitis (UC)) and 30 HCs. Effect of lnc-ITSN1-2 on IBD CD4+ T cell activation, proliferation and differentiation was determined and its regulatory interaction with miR-125a and IL-23R was detected. Results: 309 upregulated and 310 downregulated lncRNAs were identified in IBD patients by RNA-Sequencing, which were enriched in regulating immune and inflammation related pathways. Large-sample qPCR validation disclosed that both intestinal mucosa and PBMC lnc-ITSN1-2 expressions were increased in IBD patients compared to HCs, and presented with good predictive value for IBD risk especially for active disease conditions, and they positively correlated with disease activity, inflammation cytokines and IL-23R in IBD patients. Lnc-ITSN1-2 was decreased after infliximab treatment in active-CD patients. Besides, lnc-ITSN1-2 promoted IBD CD4+ T cell activation and proliferation, and stimulated Th1/Th17 cell differentiation. Multiple rescue experiments disclosed lnc-ITSN1-2 functioned in IBD CD4+ T cells via targeting miR-125a then positively regulating IL-23R. Luciferase Reporter assay observed that lnc-ITSN1-2 bound miR-125a, and miR-125a bound IL-23R. Conclusion: Lnc-ITSN1-2 correlates with increased disease risk, activity and inflammatory cytokines of IBD, as well as promotes IBD CD4+ T cell activation, proliferation and Th1/Th17 cell differentiation by serving as a competing endogenous RNA for IL-23R via sponging miR-125a.